Serum Troponin T Concentrations Are Frequently Elevated in Advanced Skin Cancer Patients Prior to Immune Checkpoint Inhibitor Therapy: Experience From a Single Tertiary Referral Center - Kurzhals, Jonas K.; Graf, Tobias; Boch, Katharina; Grzyska, Ulrike; Frydrychowicz, Alex; Zillikens, Detlef; Terheyden, Patrick; Langan, Ewan A. (Frontiers in Medicine, 2021)
Immune checkpoint inhibitor (ICI) therapy has revolutionized the treatment of several human malignancies, particularly metastatic skin cancer. However, immune-related myocarditis (irM), an immune-mediated adverse event (irAE), is often fatal. In the absence of a reliable biomarker, measurement of pre-ICI therapy serum troponin concentration has been proposed to identify patients at risk of developing irM, although real-world studies examining this strategy are lacking. Thus, we retrospectively analyzed the case records of all patients who commenced ICI therapy between January 2018 and December 2019 in a single university skin cancer center (n=121) to (i) determine the incidence of irM, (ii) establish the frequency of pre-treatment serum hsTnT elevations and (iii) to establish whether this identified patients who subsequently developed irM. Only one patient developed irM, resulting in an overall incidence of 0.8%. Pre-treatment hsTnT was measured in 47 patients and was elevated in 13 (28%). Elevated serum hsTnT concentrations were associated with chronic renal failure (p=0.02) and diabetes (p<0.0002). Pre-treatment hsTnT was not elevated in the patient who developed fulminant irM. Pre-immunotherapy serum hsTnT concentrations were often asymptomatically elevated in patients with advanced skin cancer, none of whom subsequently developed irM during ICI therapy. However, large studies are required to assess the positive and negative predictive value of hsTnT for the development of irM. In the meantime, elevated hsTnT concentrations should be investigated before initiation of immunotherapy and closely monitored during early treatment cycles, where the risk of irM is greatest.